COMPARISON OF METABOLIC PARAMETERS IN CHILDREN AND ADOLESCENTS WITH AND WITHOUT INSULIN RESISTANCE - Leandro Coelho Lemos; Claudio Shigueki Suzuki; Aristides Miguel da Costa Machado-Rodrigues; William Cordeiro de Souza; Sandra Aires Ferreira; Adriana Masiero Kühl; Timothy Gustavo Cavazzotto; Marcos Roberto Queiroga; Luis Paulo Gomes Mascarenhas (Journal of Physical Education)
ABSTRACT The aim of the study was to compare the behavior of metabolic parameters, blood pressure, and obesity indicators in children and adolescents with and without insulin resistance. Sixty-one overweight children (6 to 18 years) underwent anthropometric measurements of body mass (BM), height and waist circumference (WC), blood pressure (BP), bioimpedance (relative (%F) and absolute fat (BF)), and blood collection for determination of glucose, insulin, and lipid profile (TG, CT, HDL-C, LDL-C). The BMI z-score was used to classify nutritional status and the HOMA-IR index (> 2.5) for insulin resistance. Participants were divided into two groups, insulin resistant (IR, n= 27) and non-insulin resistant (NIR, n= 33). Regardless of age, children and adolescents with excess weight and IR presented higher BM, WC, BMI, %F and BF (kg), TG, and plasma insulin than their NIR counterparts, who in turn presented higher LDL-C. The groups did not differ in nutritional status (BMI z-score); however, in the comparison between the undesired proportions of the metabolic components, only three presented alterations with significant differences between the groups (TC, LDL-C, and TG). It is concluded that IR influences the development of dyslipidemias in this age group, especially TG.